2021
DOI: 10.1016/j.amsu.2021.102779
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of effectiveness and safety of Niclosamide as add on therapy to the standard of care measures in COVID-19 management

Abstract: Background COVID-19 pandemic has ignited the urge for repurposing old drugs as candidate antiviral medicines to treat novel challenges of viral infections. Niclosamide (NCS) is an anti-parasitic drug of known antiviral potential. Therefore, this study attempts to investigate the antiviral effect and safety of NCS on SARS-CoV-2 caused COVID-19 patients. Methods Randomized controlled open label clinical trial encompassed 75 COVID-19 patients treated with standard of care … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…A phase I trial showed that intranasal and inhalation administration of niclosamide exhibited dose-dependent pharmacokinetics, and was well-tolerated in healthy volunteers (Backer et al, 2021). Niclosamide add-on therapy was beneficial for reducing the time needed for recovery (5 vs. 7 days, p = 0.005), but it did not reduce mortality from SARS-CoV-2 infection (Abdulamir et al, 2021). Currently, eight relevant clinical trials on niclosamide have been registered.…”
Section: Inhibitors Of Endosomal Entrymentioning
confidence: 99%
“…A phase I trial showed that intranasal and inhalation administration of niclosamide exhibited dose-dependent pharmacokinetics, and was well-tolerated in healthy volunteers (Backer et al, 2021). Niclosamide add-on therapy was beneficial for reducing the time needed for recovery (5 vs. 7 days, p = 0.005), but it did not reduce mortality from SARS-CoV-2 infection (Abdulamir et al, 2021). Currently, eight relevant clinical trials on niclosamide have been registered.…”
Section: Inhibitors Of Endosomal Entrymentioning
confidence: 99%
“…A trial proved that Niclosamide has relatively safe clinical benefits in COVID-19 management. Compared with the control group, the cure rate of the Niclosamide treatment group increased [79] . Niclosamide has poor oral bioavailability due to its limited water solubility.…”
Section: Drugs Targeting the Sars-cov-2 Life Cyclementioning
confidence: 86%
“…Whether the delivery of NIC in nasal mucosa, rather than in the lower respiratory system, will be sufficient to inhibit inflammasome activation and ameliorate severe cases of COVID-19 is unknown. Nonetheless, prospective clinical trials including NIC already indicated the preliminary yet positive effects of NIC for treatment of hospitalized patients ( 53 , 54 ). There are currently more than 20 ongoing clinical trials using NIC in different conditions, some of them registered for COVID-19 in the ClinicalTrials.gov clinical trials registry ( 55 ).…”
Section: Discussionmentioning
confidence: 99%